Penerapan Green Office pada Food and Beverage Department dalam Peningkatan Kepedulian Lingkungan di Sheraton Bandung Hotel & Towers - Nur Fadlilah Maghfiroh Kusuma Ningrum (Journal of Mandalika Review, 2023)
The tourism industry is one of the largest industries in the world, environmentally friendly tourism has now become the trend most in demand by world tourists. The food and beverage department is closely related to the cleanliness and satisfaction of guests because it is responsible for food and beverages. Green office is one of the efforts of the food and beverage department in creating a clean, beautiful, comfortable work environment, as well as healthy and does not interfere with the surrounding environment. Using qualitative descriptive research methods, this study aims to find out how the application of green office in the food and beverage department and how it relates to efforts to increase environmental awareness. Five indicators of the application of the green office concept used, namely, electricity savings, water savings and conservation, office waste management, greening, other effort. The result showed that in a score of 80% which shows that the application of the green office concept in the food and beverage department at Sheraton Bandung Hotel & Towers is quite implemented. The distribution of the level of implementation in accordance with the implementation indicators is electricity savings (75%), water savings and conservation (75%), office waste management (100%), greening (50%), other efforts (100%). With the implementation of green office, Sheraton Bandung Hotel & Towers can increase concern for the environment as evidenced by the decrease in electricity costs by 0.34% per year from before the implementation of the green office.